Callus induction and cell culture of castor (Ricinus communis L. CV. Shabje) (Journal of Bio-Science, 2014)
Context: Tissue culture is an important tool in plant biotechnology that allows for an increase in biomass or metabolite production by utilizing several techniques in callus or cell cultures. Ricin is a toxic protein that can be extracted from the castor bean as secondary metabolite. The ricin has been used experimentally in medicine to kill cancer cell. We developed callus and cell culture technique for the possible extraction of ricin from the cell suspension culture of Ricinus communis. Objectives: The present investigation aimed to develop the cell culture technique of R. communis L. cv. Shabje and tried to establish a protocol for cell suspension culture of castor for possible extraction of ricin from cell extract. Materials and Methods: The hypocotyl explants of R. communis L. cv. Shabje were used as experimental materials. Cultured on Murashige and Skoog medium supplemented with different concentrations and combinations of BAP, NAA, 2,4-D and IAA for callus induction. For cell culture, the media were used without agar with different concentrations and combinations of these hormones. Results: For callus induction the combination of BAP 2.0 mg/l + 0.5 mg/l NAA showed the best performance but in case of cell culture the combination of BAP 2.0 mg/l and 0.2 mg/l NAA showed the best result. Conclusion: The present investigation clearly established and demonstrated the method of obtaining cell suspension culture and important secondary metabolite ricin could be obtained from cell suspension culture of R. communis L. holding promises to explore cell culture industry for ricin production. DOI: http://dx.doi.org/10.3329/jbs.v20i0.17738 J. bio-sci.  20:  161-169, 2012